2001
DOI: 10.1161/hq1101.0908551
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Coordinated Changes in HDL and LDL Size Phenotypes

Abstract: Abstract-We investigated the correlation of high density lipoprotein (HDL) and low density lipoprotein (LDL) particle size distributions in samples from Ͼ1100 participants in the San Antonio Family Heart Study. By use of analyses of individual correlations of each HDL fraction with each LDL fraction, we devised new metrics for particle size phenotype, termed ⌬HDL and ⌬LDL, to optimally reflect the size correlations. Confirming previous studies, we found that the 2 size phenotype variables were positively corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 59 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…The heritability of adiponectin concentration in this sample is 0.59 (P ϭ 3.7 ϫ 10 Ϫ10 ), supporting the previous finding of a substantial additive genetic component to variation in this trait in a population of northern European ancestry (14). All other traits we examined are significantly heritable in our sample (Table 3), consistent with previous findings (7,11,12,15) in this population. Genetic and environmental correlations.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The heritability of adiponectin concentration in this sample is 0.59 (P ϭ 3.7 ϫ 10 Ϫ10 ), supporting the previous finding of a substantial additive genetic component to variation in this trait in a population of northern European ancestry (14). All other traits we examined are significantly heritable in our sample (Table 3), consistent with previous findings (7,11,12,15) in this population. Genetic and environmental correlations.…”
supporting
confidence: 91%
“…Metabolic syndrome phenotypes. SAFHS participants have been measured for anthropometric traits and a number of biochemical phenotypes, as described elsewhere (7,11,12). For comparison to ICAM-1, we chose phenotypes relating to four aspects of the metabolic syndrome (1): 1) glucose homeostasis (fasting plasma glucose and insulin levels, glucose and insulin levels at 2 h after oral glucose challenge, and the homeostasis model assessment of insulin resistance [13]), 2) obesity (BMI, waist circumference, and serum levels of the adipose cytokines leptin [7] and adiponectin [14]), 3) hypertension (systolic and diastolic blood pressure), and 4) dyslipidemia (plasma total cholesterol, LDL cholesterol, LDL median particle diameter, total HDL cholesterol, HDL3 cholesterol subfraction, and triglycerides).…”
mentioning
confidence: 99%
“…36 Deng et al 37 found that ER-a gene was associated with BMI variation in healthy Caucasian women. In addition to its role in obesity phenotypes, ER-a plays a distinct physiological role in mediating the specific effects of estrogen on the growth, differentiation and function of reproductive tissues.…”
Section: Discussionmentioning
confidence: 99%
“…HDL and LDL particle sizes were measured by composite gradient gel electrophoresis as described previously ( 19,(28)(29)(30).…”
Section: Effects Of Rosuvastatin On Charge-based Ldl and Sdldl Subframentioning
confidence: 99%